The effect of additional Effective Microorganism (EM) on vegetative growth of aerobic paddy / Nurulnathasa Amirullah - Amirullah, Nurulnathasa (Faculty of Plantation and Agrotechnology, 2019)
This study was conducted to evaluate the effect of additional EM on aerobic rice cultivation. The objective of this study was to determine the effect of additional EM on the growth pattern, and to evaluate the efficiency of EM uptake on the aerobic plant. This experiment was carried out by using RCBD consisted of three treatments with two replications in four blocks. Aerobic seed cv. Aeron1 was used as planting materials and has been applied by three different treatments of EM during vegetative growth. The first treatment (T1) as a control, applied with recommended chemical fertilizer (normal practices) with 1.8g NPK + 0.9g Urea with no additional of EM. Second treatment (T2) consisted of 1.8g NPK + 0.9g Urea + 100ml EM-4 solution and third treatment (T3) was treated with 0.9 g NPK + 0.9g Urea + 100ml EM-4. Plant growth parameters were collected at three series of harvesting at 35, 50, 63 DAS. Result shown that there was no significant differences between treatments for all parameters studied (plant biomass, number of tillers, absolute growth rate and relative growth rate). The result shown that the growth pattern during third harvesting was more rapid by T3. Application of T3 showed that the highest numbers of tillers (seven tillers per plant), plant dry mass (57.74g per plant) and AGR (13.82g per week). However, T2 obtained the highest value in mean RGR (765 mg per week). As a conclusion, application of additional EM was not improved plant growth parameter of aerobic rice cultivation however the increment pattern of plant growth was rapid particularly by using additional EM (0.9 g NPK + 0.9 Urea + 100 ml EM).